Shared Medical Appointments in Pulmonary Hypertension. (1st March 2014) - Rahaghi, Franck F.; Chastain, Veronica L.; Benavides, Rosanna; Ferrer, Gustavo; Ramirez, Jose; Mehta, Jinesh; Oliveira, Eduardo; Smolley, Laurence
Abstract : We aimed to adapt the shared medical appointment (SMA) model to the care of pulmonary hypertension (PH) patients and evaluate patient satisfaction. Our SMA team included a PH specialist, a PH nurse, and one research fellow. Eight to twelve PH patients with a family member were invited during office visits and by phone calls. Attendance was verified and encouraged by phone calls and informational letters. The meetings started with a 30‐minute presentation on various PH topics, which was followed by each patient's individual visit and a focused examination in front of the group, allowing group questions and interaction. Of the total number of patients ( n = 53), 84% stated that they would attend a future SMA. The care provided was rated excellent to very good by 98% of the patients. Ninety‐two percent stated that they improved their understanding of the disease and treatment options, and 59% acknowledged a preference for the group visit over the private visit. Twenty‐five percent of patients stated that they were very likely to likely to some extent to agree to change or seek a change in treatment modality on the basis of conversation with other patients in the SMA. The majority of our patients expressed no privacy concerns before the meeting (76%), and even more expressed no such concerns afterward (88%). In conclusion, the SMA model allows PH patients to increase understanding of their disease process while integrating peer support, promoting social interaction, and addressing patients' emotional needs. Other (rare) pulmonary diseases may benefit from this model.